KASUS TUBERKULOSIS DENGAN RIWAYAT DIABETTES MELLITUS DI WILAYAH PREVALENSI TINGGI DIABETTES MELLITUS - Hendra Rohman (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
Tuberculosis (TB) and diabetes mellitus (DM) are both important health issues. A bidirectional association between them has been demonstrated. The link of DM and TB was more prominent in developing countries where TB is endemic and the burden of diabetes mellitus is increasing. The association between diabetes and tuberculosis may be the next challenge for global tuberculosis control worldwide. Proper planning and collaboration are necessary to reduce the dual burden of diabetes and TB. In order to encourage the implementation of TB prevention programs, data and information are needed in the information system. An integrated and integrated TB programming information system. Spatial analysis with an information system is a device that can detect of hight risk areas, so it can help for handling and control. TB patients with DM 2014 in the Kulon Progo regency, there were 16 people. Spatial analysis using GeoDa TM software version 1.6.6, and ArcGIS version 10.1.The spatial interaction model is a classical regression model that there have significant correlation between DM population with pulmonary TB-DM incidence, with p value = 0.03776, but no spatial dependence. TB control strategy through TB development program. TB program storage program and DM holder in Dinas Kesehatan want to do monitoring to monitor lung tuberculosis patient with history of DM